2022
DOI: 10.1186/s12870-022-03724-4
|View full text |Cite
|
Sign up to set email alerts
|

Differential seedling growth and tolerance indices reflect drought tolerance in cotton

Abstract: Background Cotton production is adversely effected by drought stress. It is exposed to drought stress at various critical growth stages grown under a water scarcity environment. Roots are the sensors of plants; they detect osmotic stress under drought stress and play an important role in plant drought tolerance mechanisms. The seedling stage is very sensitive to drought stress, and it needed to explore the methods and plant characteristics that contribute to drought tolerance in cotton. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…Less water supply towards seed also slows down the process of hydrolyzation of stored carbohydrate reserves, which ultimately affects the transport of food to developing embryo, restricting radicle emergence from seed coat, hence reducing germination (Channaoui et al, 2019). In cotton, root morphology has been shown to play significant role in conferring tolerance to drought especially at seedling stage (Singh et al, 2018;Mahmood et al, 2022). Pace et al (1999) observed that cotton seedlings showed increased thickness and length of roots when subjected to drought stress as compared to the control seedlings.…”
Section: Seedling Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Less water supply towards seed also slows down the process of hydrolyzation of stored carbohydrate reserves, which ultimately affects the transport of food to developing embryo, restricting radicle emergence from seed coat, hence reducing germination (Channaoui et al, 2019). In cotton, root morphology has been shown to play significant role in conferring tolerance to drought especially at seedling stage (Singh et al, 2018;Mahmood et al, 2022). Pace et al (1999) observed that cotton seedlings showed increased thickness and length of roots when subjected to drought stress as compared to the control seedlings.…”
Section: Seedling Stagementioning
confidence: 99%
“…Modification of root system has been shown to increase drought tolerance in plants (Vivek et al, 2017). Deep root systems confers high drought tolerance to plants by increasing mineral and water uptake (Mahmood et al, 2022).…”
Section: Root System Architecture (Rsa)mentioning
confidence: 99%
“…Moreover, morphological attributes, including plant height (cm), stem diameter (mm) and leaf area (mm 2 ) were also recorded. The tolerance index was calculated using the methodology explained by Mahmood et al (2022). Moreover, factorial analysis of variance (ANOVA) was used to estimate the difference among genotypes, treatments, and replicates.…”
Section: Screening Of Genotypesmentioning
confidence: 99%
“…Many previous studies have evaluated salt-stress adaptive changes in flax populations during germination [ 36 , 37 ]. Indicators such as germination rate, root length, and shoot length effectively reveal the behavioral adaptation of flax to salt stress during the germination period [ 38 , 39 ]. Abido et al [ 40 ] found that Egyptian flax cultivars showed wide natural variation in adaptation to salinity, and the Giza11 cultivar exhibited a higher germination rate and speed at high salinity levels compared with other cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Some flax cultivars are salt-tolerant during germination but salt-sensitive during the vegetative phase [ 42 ]. The seedling stage is an important period for crop growth and yield [ 8 , 38 ]; however, adaptive changes in flax seedlings under salt stress have been less studied. In particular, no transcriptional profiles other than Wu’s limited study [ 43 ], in which only 42.92% of RNA reads were mapped to the reference genome, have shown differentially expressed genes (DEGs) to analyze the difference in adaptability between flax cultivars under salt stress.…”
Section: Introductionmentioning
confidence: 99%